Influence of Microplastics on Microbial Structure, Function, and Mechanical Properties of Stream Periphyton - Merbt, Stephanie N.; Kroll, Alexandra; Tamminen, Manu; Rühs, Patrick A.; Wagner, Bettina; Sgier, Linn; Sembalova, Olga; Abel, Bernd; Tlili, Ahmed; Schirmer, Kristin; Behra, Renata (Frontiers in Environmental Science, 2022)
Periphyton is a freshwater biofilm composed of prokaryotic and eukaryotic communities that occupy rocks and sediments, forming the base of the food web and playing a key role in nutrient cycling. Given the large surface that periphyton comprises, it may also act as a sink for a diverse range of man-made pollutants, including microplastics (MP). Here we investigated the effect of 1–4 μm and 63–75 µm sized, spherical polyethylene MP with native and ultraviolet (UV)-weathered surface on developing natural stream periphyton communities over 28 days. In order to ensure proper particle exposure, we first tested MP suspension in water or in water containing either Tween 80, extracellular polymeric substances – EPS, fulvic acids, or protein. We found the extract of EPS from natural periphyton to be most suitable to create MP suspensions in preparation of exposure. Upon exposure, all tested types of MP were found to be associated with the periphyton, independent of their size and other properties. While biomass accrual and phenotypic community structure of the photoautotrophs remained unchanged, the prokaryotic and eukaryotic communities experienced a significant change in composition and relative abundances. Moreover, alpha diversity was affected in eukaryotes, but not in prokaryotes. The observed changes were more prominent in periphyton exposed to UV-treated as compared with native surface MP. Mechanical properties, as assessed by compression rheology, showed that MP-exposed periphyton had longer filamentous streamers, higher stiffness, lower force recovery and a higher viscoelasticity than control periphyton. Despite the observed structural and mechanical changes of periphyton, functional parameters (i.e., photosynthetic yield, respiration and nutrient uptake efficiencies) were not altered by MP, indicating the absence of MP toxicity, and suggesting functional redundancy in the communities. Together, our results provide further proof that periphyton is a sink for MP and demonstrate that MP can impact local microbial community composition and mechanical properties of the biofilms. Consequences of these findings might be a change in dislodgement behavior of periphyton, a propagation through the food chains and impacts on nutrient cycling and energy transfer. Hence, taking the omnipresence, high persistence and material and size diversity of MP in the aquatic environment into account, their ecological consequences need further investigation.